Analisis Kepuasan Anggota terhadap Kualitas Pelayanan Melalui Google Review di BMT Beringharjo Nganjuk - Rizky Atus Sholikhah; Riza Taufiqi Majid (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2025)
This study aims to analyze members’ satisfaction with service quality at BMT Beringharjo Nganjuk Branch by utilizing secondary data in the form of Google Reviews during the 2021–2025 period. The research employs a quantitative approach with secondary data analysis through content analysis of 87 reviews submitted by members. Of the total reviews, 85 provided five-star ratings and two provided four-star ratings, indicating a very high level of member satisfaction. The analysis results show that the reliability and responsiveness dimensions are the most dominant contributors to member satisfaction, while the empathy and tangibles aspects still require improvement. Factors such as service speed, staff friendliness, transaction convenience, and cash pick-up services serve as the main indicators shaping members’ positive perceptions of BMT. These findings reinforce the theory that service quality has a significant influence on member satisfaction and loyalty in Islamic microfinance institutions. Therefore, BMT Beringharjo Nganjuk is expected to continuously strengthen digital-based service strategies and interpersonal relationships to maintain member trust and satisfaction in the era of technology-driven transformation of Islamic financial services.